Applying Frame Semantics to Translation: A Practical Example - Rojo López, Ana María (Meta, 2002)
AbstractThis work intends to illustrate some of the contributions the semantic theory known as ‘Frame Semantics’ can make to the translation of cultural elements. The study starts by defining the objectives and basic concepts that constitute our model of analysis. Secondly, a typology of frames for the analysis of our examples is proposed. Later on, this typology is applied to the analysis of a number of examples extracted from David Lodge’s novel Small World and its translation into Spanish El Mundo es un Pañuelo. Finally, we summarize the main conclusion of the study.